Differential diagnosis of acute coronary syndrome учебное пособие - Eniseeva E. S. (Иркутск, ИГМУ, 2022)
Recommended by the CCMС of FSBEI HE ISMU MOH Russia as a study guide for foreign students mastering educational programs of higher education by the educational program of the specialty of General Medicine for mastering the discipline “Physics, mathematics”